EAM potential (LAMMPS cubic hermite tabulation) for the Ni-Co system developed by Pun, Yamakov and Mishin (2015) v000 - Yamakov, Vesselin; Mishin, Yuri; Purja Pun, Ganga (OpenKIM, 2018)
EAM potential for the Ni-Co system developed by Pun, Yamakov and Mishin (2015) by fitting to experimental and first-principles data.
Keywords: OpenKIM; Model; MO_010613863288_000